Impact of Nigella sativa oil on glycemic control in alloxan-induced diabetic Wistar rats - Christian, Onahinon; Ogli, Sunday; Akwaras, Nndunno; Adugba, Augustine Oko; Obochi, Godwin (International Journal of Research in Medical Sciences, 2024)
Background: To effectively manage diabetes, it is crucial to achieve optimal glycemic control by ensuring that A1C levels remain below 7.0%. This study aimed to investigate the impact of Nigella sativa oil (black seed oil, BSO) on glycemic control in alloxan-induced diabetic Wistar rats. Methods: Forty (40) male Wistar rats weighing 200-250 gm were randomly allocated into eight (8) groups of five (5) animals per group. Group 1 received normal saline as the normoglycemic control, while groups 2 to 8 were given alloxan monohydrate to induce hyperglycemia, following the method of Osikwe et al. Following the induction of hyperglycemia, group 2 received normal saline, group 3 received 200 mg/kg of metformin, group 4 received 2 mg/kg of glimepiride, group 5 received 2.5 ml/kg of BSO, group 6 received glimepiride and BSO, group 7 received metformin and BSO, and group 8 received BSO, glimepiride, and metformin. Results: The results showed that BSO significantly reduced fast blood glucose levels compared to the diabetic control group (p<0.05), lowered glycosylated hemoglobin to <7%, and improved pancreatic beta cell function. Conclusions: Black seed oil reduces fasting blood glucose, exhibits synergism with glimepiride, and improves pancreatic beta-cell function in alloxan-induced diabetic Wistar rats.